Performance measurement of mosques based on Maqasid Al-Syariah in Malaysia: governance of resources, processes and outputs / Muhd Fauzi Abd. Rahman - Abd. Rahman, Muhd Fauzi (2017)
The main objective of this study is to examine factors influencing the performance of mosques in Malaysia. As existing frameworks measuring mosque performance is lacking for comparison, this research is limited to the performance measurement frameworks based on for-profit and non-profit organisations. This study also fills the void by investigating the variables affecting the performance of mosques, as remarkably unique entities. In essence, it seeks to investigate the relationship between the four main variables of performance measurement comprising resources, processes, outputs and outcomes. The fifth variable included in this performance measurement framework is governance, which was tested for its influence on resources and outputs respectively. While variables such as the resources, processes and outputs of mosques can be hypothesized, mosques also have many Syariah objectives as non-profit organisations such as preserving faith, preserving intellect and public interest. These objectives are used in this study as proxy measures of outcomes in the form of the Maqasid Syariah Index. Hence, outcome as a construct in this study is replaced by Maqasid Syariah Index. The survey was conducted throughout Malaysia, including Sabah and Sarawak. Given the population size and the vast geographical area to be covered, self-administered questionnaires survey by mail was used as the main method of data collection. A set of questionnaires in the form of booklet and a self-addressed postage paid envelopes were mailed to 800 mosques selected randomly across the states of Malaysia. Out of the 224 questionnaires returned, 210 were usable and valid for analyses. The resulting data was analysed using Structural Equation Modelling (SEM) and the findings of the study contribute to advancing understanding of mosque performance in several important ways. First, the mediation role of processes becomes a full mediator between resources and outputs. Second, governance has a positive influence on the resources and outputs of mosques in the performance measurement framework. Third, the Maqasid Syariah Index is found to be negatively significant, thus indicating that as outputs are increased, the overall Maqasid or objectives of the mosques shows a reduction, instead of increase in performance. The findings from this study will benefit various stakeholders of the mosques especially those related to the management, congregation and religious authorities whom are directly affected by the mosques' performance. As relatively few researches have been done in this area, the findings of the study provide empirical evidence on the direct and indirect relationships between governance, resources, processes and outputs of mosques. It is worth noting that despite the perceived uniqueness of the mosques as religious-based non-profit organisations, this study shows that lessons from the private sectors' performance measurement can also be applied to non-profit entities.